2021
DOI: 10.1001/jamadermatol.2021.0793
|View full text |Cite
|
Sign up to set email alerts
|

A Mutational Survey of Acral Nevi

Abstract: cral melanoma is a rare melanocytic tumor that arises on the non-hair-bearing skin of the palms, soles, and nail beds. 1 Unlike cutaneous melanoma, acral melanoma is not linked to UV radiation exposure; it exhibits a much lower point mutation burden than cutaneous melanoma but a higher frequency of structural variants and copy number alterations. 2,3 The incidence of acral melanoma is uniform across all populations, making it the most common melanoma subtype in individuals of African, Asian, and Hispanic desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…This raises the possibility that melanomas on acral are of two different types, with a bona fide and unique acral type with an admixture of cutaneous melanoma of the World health Organization (WHO) low-CSD subtype, i.e., melanomas on the sun-exposed skin with low degree of cumulative sun damage [ 89 ]. A recent study on acral nevi identified BRAF V600E mutation in 86% of samples [ 90 ], which is similar to what was observed in cutaneous nevi that considered the precursors of low-CSD melanomas [ 45 ]. Another study identified transcriptome-level differences between acral and cutaneous melanocytes [ 91 ].…”
Section: Discussionsupporting
confidence: 68%
“…This raises the possibility that melanomas on acral are of two different types, with a bona fide and unique acral type with an admixture of cutaneous melanoma of the World health Organization (WHO) low-CSD subtype, i.e., melanomas on the sun-exposed skin with low degree of cumulative sun damage [ 89 ]. A recent study on acral nevi identified BRAF V600E mutation in 86% of samples [ 90 ], which is similar to what was observed in cutaneous nevi that considered the precursors of low-CSD melanomas [ 45 ]. Another study identified transcriptome-level differences between acral and cutaneous melanocytes [ 91 ].…”
Section: Discussionsupporting
confidence: 68%
“…In parallel, copy-number variants (CNV) intensively favor potential driver genes in acral melanoma that thus exhibit a heavy CNV mutational burden ( 3, 5 ). However, Smalley and colleagues have analyzed the genome data and demonstrated that acral nevi are not precursors to the majority of prototypical acral melanomas, indicating that acral melanoma has an evolutionary trajectory different from that of cutaneous melanoma ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that CNVs were much less common in acral melanocytic nevus than acral melanoma. A mutational survey of acral melanocytic nevi was also performed in a U.S. population [ 12 ]. Similarly to the Korean results, BRAF mutation was commonly observed in acral melanocytic nevus.…”
Section: Acral Melanocytic Nevusmentioning
confidence: 99%
“…The lesions are benign, and progression to melanoma is rare. Most acral melanomas arise de novo, not in association with a preexisting acral nevus [ 12 , 29 ]. Acral melanocytic nevi which do not show typical benign dermoscopic patterns may require clinical and dermoscopic surveillance, and once or twice a year is enough [ 30 ].…”
Section: Acral Melanocytic Nevusmentioning
confidence: 99%